Stigmasterol Exerts an Anti-Melanoma Property through Down-Regulation of Reactive Oxygen Species and Programmed Cell Death Ligand 1 in Melanoma Cells - Na-Ra Han; Hi-Joon Park; Seong-Gyu Ko; Phil-Dong Moon (MDPI AG, 2024)
Cancer immunotherapy as a promising anti-cancer strategy has been widely studied in recent years. Stigmasterol (STIG), a phytosterol, is known to have various pharmacological effects, including anti-inflammatory effects. However, the pharmacological role of STIG on melanoma immunotherapy has not been investigated. The present study demonstrates the anti-melanoma potency of STIG through the regulation of PD-L1 levels. The results reveal that STIG reduces reactive oxygen species (ROS) levels induced by hydrogen peroxide and increases glutathione levels decreased by α-MSH in B16F10 cells. Moreover, STIG significantly decreases melanin content and tyrosinase activities elevated by α-MSH. It also suppresses nitric oxide production induced by α-MSH. Additionally, STIG induces apoptosis with the up-regulation of PARP activation. STIG inhibits IFN-γ-induced PD-L1 expression and STAT1 phosphorylation levels. STIG also reverses the up-regulation of PD-L1 and phosphorylated STAT1 levels augmented by cisplatin, and STIG enhances CD8(+) T-cell-mediated cell death against B16F10 cells. These findings represent the first evidence of pro-apoptotic activity of STIG on melanoma cells through the down-regulation of ROS and PD-L1 pathways. Therefore, STIG may be an effective candidate for melanoma immunotherapy.